PERLINDUNGAN HUKUM DEBITUR DALAM PENYELESAIAN SENGKETA ATAS KPR YANG MACET DALAM PERJANJIAN KREDIT KEPEMILIKAN RUMAH DI BANK BTN CAB SAMARINDA - Riyos Wahyudi (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTThe need for a home is a basic necessity of human life, will the house have things easy. Given the increasingly high prices, many people are hard. Khilafah children of the nation. Banks as a financing institution help the government reduce the economic problems of the community associated with the problem. The Bank provides a Home Ownership Credit that can be used to buy a house with debt to the bank. Proven credit is quite effective to help the community. But in practice, credit travel is not always smooth. In essence, the people who borrow from the banks are economically weak, it may be in the event of a disaster or things outside which they can not repay their debts to the bank. Then there will be a dispute called bad credit. Banks surely will surely arise such circumstances, how the bank prepares itself for normal circumstances? What efforts can the bank make to repay the loan?In this case, means the house as well as a collateral for the debtor's loan. If the debtor can no longer repay the debt, the bank will cooperate with the State Wealth Service Office and Auction (KPKNL) to hold an auction on the house of the warranty. The results of the auction will be used as a bank instead of the debtor's debts that are not paid.